Statutory interpretation and the rule of law in Ireland - Curran, Cathal (Trinity College (Dublin, Ireland). School of Law, 2014)
This PhD thesis addresses the theory that the default preference for literal interpretation in the statutory context instantiates a formal conception of the rule of law. This claim is reflected in the Irish constitutional framework, which centres on the law making role of the legislature and envisages a restrictive interpretative role of the courts in light of this. The theory holds that in their reticence to depart from the literal rule judges comply with the rule of law, ensuring both non-arbitrariness in adjudication and the predictability of law by channeling the literal implications of statutory texts and not their own biases or values. I will argue that this claim cannot be substantiated. This will be based on an analysis of a number of key issues to the interpretative theory outlined.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin